STUDENT TEACHER DISPOSITIONSATTHE ENGLISH EDUCATION STUDY PROGRAM FACULTY OF TEACHER TRAINING AND EDUCATION UNIVERSITY OF TANJUNGPURA PONTIANAK - Rahayu Apriliaswati (ICoTE Proceedings)
The role of Teacher Training and Education Faculty is to prepare student teachers not only on the knowledge and teaching skills but also dispositions.The purpose of this descriptive study was to investigate the dispositions of student teachers at English Education study program of Teacher Training and Education Faculty of Tanjungpura University Pontianak. It was conducted through the participation of 10 lecturers who have been teaching the fourth semester students in 2016/2017 academic years. In the study, a questionnaire with totally 76 items of teacher disposition indicators was administered. Based on the result of questionnaire analysis, only a few lecturers (<1%) thought that the dispositions of student teachers were very positive and 80% lecturers stated that the student teachers’ dispositions needed to be paid attention and developed during their study especially in performing professionalism; showing enthusiastic attitudes, demonstrating effective oral and written communication skills; showing consistent learners.